2007
DOI: 10.1127/0935-1221/2007/0019-0125
|View full text |Cite
|
Sign up to set email alerts
|

Roman quarries of the Iberian peninsula: "Anasol" and "Anasol"-type

Abstract: The Iberian peninsula is rich in marble, both white and coloured, of excellent quality, used in the past (Pliny NH, XXXVI, II) and also at the present time as material for building and decoration. Many types of these marbles are similar to some, better known, Greek, Italian, Egyptian and Asian marbles. During the Roman Empire "marmor carystium" was extensively used. Taking into account the great similarity of this marble with the "anasol" and "anasol"-types mined in Spain and Portugal, this work presents a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Petrographic data show lepidoblastic textural features more similar to those found in Almadén de la Plata, to which we must add high MgO content in comparison to the varieties of the Estremoz Anticline. On the other hand, these textures are associated with marbles rich in dolomite, as already previous studies have pointed out (Morbidelli et al, 2007; Ontiveros et al, 2012; Tucci et al, 2010). Although these textural varieties have not yet been found on current quarry fronts, especially the most detritic levels of greenish coloration that characterizes this variety, the presence of greyish varieties rich in dolomitic has been verified.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Petrographic data show lepidoblastic textural features more similar to those found in Almadén de la Plata, to which we must add high MgO content in comparison to the varieties of the Estremoz Anticline. On the other hand, these textures are associated with marbles rich in dolomite, as already previous studies have pointed out (Morbidelli et al, 2007; Ontiveros et al, 2012; Tucci et al, 2010). Although these textural varieties have not yet been found on current quarry fronts, especially the most detritic levels of greenish coloration that characterizes this variety, the presence of greyish varieties rich in dolomitic has been verified.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, in some cases, there are doubts on the varieties, whereas to their provenance, especially with types of white marbles, as well as white with green, or greyish green bands, generically known in the bibliography as cipollino . This banded variety, present in the Traianeu m of Italica , can sometimes be easily mistaken with marmor Carystium of Euboea or with other types of foreign marble, such as the cipollino of the Apuan Alps (Negri Arnoldi et al, 1999) and especially with Hispanic varieties, like 'anasol' marble of Macael (Almeria), or the so‐called Portuguese 'anasol', as well as a variety from Almadén de la Plata (Seville) (Morbidelli et al, 2007; Tucci et al, 2010). The results of the study carried out by Tucci et al (2010) on marble samples of this variety from Italica should be taken into account: 25 samples were Italian cipollino from Apuan quarries (Alps Corchiae sector), 20 from Greek quarries of Euboea, and only 6 from Hispania , specifically from Macael (Almeria) quarries.…”
Section: Introductionmentioning
confidence: 99%
“…3A-D. Stable isotope values for marbles from Italy (Attanasio et al, 2006;Cavari et al, 2012;Franzini et al, 2010), Iberia (Lapuente et al, 2000;Morbidelli et al, 2007;Origlia et al, 2011) and North Africa (Antonelli et al, 2009;Origlia et al, 2012) are shown in Fig. 3A.…”
Section: Resultsmentioning
confidence: 98%
“…No less importantly, applying this type of geochemical analysis to inscriptions of known provenance and date promises to deliver vast amounts of new information on the history of individual production centers and the shifting demand for their marbles around the ancient Mediterranean economy. (Attanasio et al, 2006;Cavari et al, 2012;Franzini et al, 2010) , Iberia (Lapuente et al, 2000;Morbidelli et al, 2007;Origlia et al, 2011) and North Africa (Antonelli et al, 2009;Origlia et al, 2012). (B) Anatolian/Turkish marbles (Attanasio et al, 2006;Attanasio et al, 2008;Attanasio et al, 2009;Brilli et al, 2015;Cahill and Lazzarini, 2014;Capedri et al, 2004;De Paepe et al, 2004;De Paepe et al, 2006;Ramage and Tykot, 2011;Sekedat, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of marbles has been available in the Mediterranean basin for over two millennia [ 3 ]. The identification of pure white marbles of Greek, Turkish, Spanish, Italian, or other origin [ 4 ], as well as their use to fabricate works of art and cultural heritage, was the subject of study by a number of scientists [ 5 , 6 ]. Indeed, a thorough scientific investigation is usually necessary in order to support and complete the work of historians and restorers [ 7 , 8 ] as, once the type of marble used to make the artistic artefacts under study has been identified, an attempt can be made to solve the problems related to restoration and conservation.…”
Section: Introductionmentioning
confidence: 99%